PENGARUH DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN YANG BERDAMPAK TERHADAP KINERJA KARYAWAN PADA PT SINERGI KALIBRASI NUSANTARA TANGERANG SELATAN - Argosawwa Rizqahu; Endang Sugiarti; Mukrodi Mukrodi (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
The purpose of this study is to determine the Influence of Work Discipline and Organizational Commitment on Employee Work Productivity which has an impact on Employee Performance at PT Sinergi Kalibrasi Nusantara South Tangerang. The method used is quantitative. The sampling technique used saturated samples and a sample of 100 respondents was obtained. Data analysis using validity test, reliability test, classical assumption test, regression analysis, determination coefficient and hypothesis test The results of this study are that work discipline has an effect on work productivity with a determination coefficient value of 87.1% and the hypothesis test obtained t count > t table or (25.709 > 1.984). Organizational commitment has an effect on work productivity with a determination coefficient value of 34.8% and hypothesis test obtained t count > t table or (7.233 > 1.984). Work discipline and organizational commitment simultaneously affect work productivity with a determination coefficient value of 87.7% with a hypothesis test obtained with a value of F calculated > F table or (34.695 > 3.080). The impact of work productivity on employee performance showed a good impact with a terminated coefficient value of 27.1 % with  a hypothesis obtained t > t table or (6.033 > 1.984).